Enhancing capsaicin solubility in lidocaine-based therapeutic deep eutectic solvents (THEDES): a COSMO-RS predictive study - Asma, Nur; Alwi, Ratna Surya; Ramadon, Delly; Mun’im, Abdul (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Capsaicin, a potent analgesic, suffers from poor aqueous solubility and low bioavailability. Therapeutic deep eutectic solvents (THEDES) have emerged as a promising platform to enhance the solubility of poorly soluble drugs. This study employed the conductor-like screening model for real solvents (COSMO-RS) for the in-silico screening of capsaicin solubility in 34 lidocaine-based THEDES, comprising 10 hydrogen bond acceptors (HBAs) and 26 hydrogen bond donors (HBDs) at 1:1 and 1:2 molar ratios. The σ-profiles and σ-potentials of the components were analysed to understand the intermolecular interactions governing solubility. Our predictions revealed a remarkable solubility range from below 1 g/L to over 437 g/L. The betaine-lidocaine (1:1) system was identified as the optimal solvent, achieving a capsaicin solubility of 437.47 g/L at 333.15 K, attributed to betaine's zwitterionic nature facilitating multifaceted hydrogen-bonding. Small polyols like ethylene glycol also performed excellently. A consistent enhancement in solubility was observed in HBD-rich (1:2) compositions and with increasing temperature. Molecular interaction analysis confirmed a robust network of conventional and non-conventional hydrogen bonds within the optimal betaine-lidocaine-capsaicin system. This work demonstrates the power of COSMO-RS as a rational design tool for formulating high-loading THEDES-based drug delivery systems, with betaine-lidocaine emerging as a top candidate for advanced capsaicin topical formulations.